EFFECT OF CRUDE SAPONIN EXTRACTED FROM ALFALFA (Medicago Sativa L) ON NEOPLASTIC AND NORMAL CELL LINES - A, Rafid Abdul Wahed (Al-Nahrain Journal of Science, 2009)
Aim of the present investigation was to assess by using (M.T.T)assay a (colorimetric assay) to measure the cytotoxic activity of crude saponin extracted from alfalfa medicago sativa L, Al-jjat, on two malignant tumor cell line (Rhabdomyosarcoma (RD) and Human epidermoid larynx carcinoma (HEP-2) cell line,and one type normal cell line Rat Embryo Fibroblast (R EF) cell line.through different exposure time (24, 48,and 72hrs) and different concentration of alfalfa crude saponin extract (1000, 500, 250, 125, 62.5, and 31 mg/ml).The Result showed that the crude saponin extracted from alfalfa have significant effects P value  0.05 on the Growth of the two maligninant cell line(RD and HEP-2 cell line) in culture in dose and time- dependant manner. Viability of cell lines decreased with time and concentration reaching its lowest after 72 hrs of treatment with the highest concentration used (1000 mg/ml).In addition, the growth of (RD) cell line was more sensitive to the alfalfa crude saponin in comparison with the growth of (HEP-2) cell line. From the other side the result showed that there is no significant effect P value  0.05 at these crude extract on the viability of normal cell line (MEF cell line). Only the Treatment with higher concentration (1000µg/ml) after 72 hrs caused significant reduction P value  0.05 in the (MEF) cell line growth.